(untitled) (World Science, 2021)
Improving the effectiveness of treatment in patients with the consequences of diaphyseal fractures of the tibia (improperly fused, unfused fractures, pseudoarthrosis, bone defects) is one of the urgent problems of traumatology, which has not only medical but also important social significance. The aim of the study is to publish clinical experience in the use of closed and semi-open blocking intramedullary metal-polymer osteosynthesis (BIMPO) in the treatment of 125 patients with consequences of diaphyseal long bones fractures. An analysis of the use of closed and semi-open blocking intramedullary metal-polymer osteosynthesis (BIMPO) in 125 patients with fracture consequences (non-fused fractures, pseudoarthrosis), who were operated with the use of 3 and 8 BIMPOF. Long-term results were observed in 103 (88.89%) patients. The consolidation of the fracture in the optimal time was noted in 98 (94.64%) patients. Within 44-90 days from the operation, resistance and limb function were restored. No case of osteomyelitis was observed. This result is rated as good. The use of new generation of intramedullary metal-polymer clamps for the treatment of bone fractures and their consequences has provided a significant reduction in surgical trauma, which optimizes the process of anatomical and functional restoration of the limb.